Charles W. Colson: a life redeemed - Aitken, Jonathan (Doubleday, 2005)
Drawing on private papers as well as interviews with colleagues, a biography of former Nixon confidant Charles W. Colson traces his political and personal odyssey from political hatchet man and Watergate felon to evangelical Christian